Penegakkan Hukum Tindak Pidana Cyberbullying Yang Dilakukan Di Media Sosial Terhadap Remaja - Pingkan D. kaunang; Febrina G.V. Kamuh; Nopesius Bawembang; Janesandre Palilingan; Andreas Lelet (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Social media is a digital communication platform that allows users to connect, interact, and share content with others through the internet. It has also become a place to build a digital identity and expand social networks. However, social media has two sides, both positive and negative. While social media offers significant benefits in terms of self-expression, it also has negative impacts, such as reducing productivity and, more dangerously, cyberbullying. In its role, social media includes various platforms like social networks, blogs, discussion forums, and others. Additionally, social media can influence social behavior, communication, and how it serves as a tool for spreading information and building relationships between individuals. The negative impact, such as cyberbullying, which occurs on social media, has reached a very dangerous level, as its consequences are severe, including damaging the mental health of the cyberbullying victims. Therefore, the purpose of this study can be based on the following problem formulation: 1. How is law enforcement conducted against cyberbullying on social media? 2. What are the obstacles in the process of stopping cyberbullying on social media? In writing this thesis, the author uses a qualitative method with a normative juridical approach, referring to existing laws that are still in force today, namely Law Number 19 of 2016 on Amendments to Law Number 11 of 2008 on Information and Electronic Transactions (ITE), Article 45, paragraph (3). However, in its implementation, this law does not directly address the issue of cyberbullying.